ANALISIS OPERASIONAL DINAS SATUAN POLISI PAMONG PRAJA DALAM MENEGAKKAN KETERTIBAN DAN KEPATUHAN TERHADAP PERATURAN DAERAH KABUPATEN SUMBAWA BARAT - MASYSYATH, HASAN; UMAR, UMAR; HUSNI, HUSNI (GANEC SWARA, 2023)
The aims of this research are; 1) To identify the level of community compliance with regional regulations implemented by the Civil Service Police Unit Service, 2) To determine the public's perception of the operations of the Civil Service Police Unit Service in upholding order in the community. This research is a qualitative descriptive study. Data collection techniques use interviews, observation and documentation. Data were analyzed using a qualitative analysis approach. Based on the data obtained, the research results show; 1) The level of community compliance is quite good in complying with regional regulations. The community is always enthusiastic about participating in socialization and campaigns for regional regulations carried out by the civil service police unit. The public in general appears to comply with various regulations that have been implemented by this agency, both in terms of environmental management, public order and other regulations. 2) Public perception of the civil service police unit in carrying out its duties and responsibilities; They always prioritize a sense of justice and respond quickly to every problem reported by the public. The Civil Service Police Unit (Satpol PP) is committed to acting fairly and proportionally in upholding order in the community.